Cooperative Secret Key Generation for Platoon-Based Vehicular Communications - Li, Kai (2019)
In a vehicular platoon, the lead vehicle that is responsible for managing the platoon's moving directions and velocity periodically disseminates messages to the following automated vehicles in a multi-hop vehicular network. However, due to the broadcast nature of wireless channels, vehicle-to-vehicle (V2V) communications are vulnerable to eavesdropping and message modification. Generating secret keys by extracting the shared randomness in a wireless fading channel is a promising way for V2V communication security. We study a security scheme for platoon-based V2V communications, where the platooning vehicles generate a shared secret key based on the quantized fading channel randomness. To improve conformity of the generated key, the probability of secret key agreement is formulated, and a novel secret key agreement algorithm is proposed to recursively optimize the channel quantization intervals, maximizing the key agreement probability. Numerical evaluations demonstrate that the key agreement probability achieved by our security protocol given different platoon size, channel quality, and number of quantization intervals. Furthermore, by applying our security protocol, it is shown that the probability that the encrypted data being cracked by an eavesdropper is less than 5%.